Antiradical activity of novel 4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole-3-thiol derivatives - A. A. Safonov; I. S. Nosulenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The process of studying free radicals began in the middle of the last century (the free radical theory of aging in 1956). Multiple studies have revealed the effect of free radicals on the cells of the body and the development of various diseases, such as diabetes, autoimmune diseases, diseases of the nervous system, and others. As a result, the term antioxidant has emerged, compounds that reduce and prevent the effects of free radicals. Most of the newly synthesized substances are studied for their antiradical properties. 1,2,4-Triazole derivatives are no exception, which has already proven themselves as biologically active compounds.